Composto orgânico e biofertilizante na nutrição do cafeeiro em formação no sistema orgânico - Araújo, João Batista Silva (2004)
Organic agriculture is a world tendency, moved by concern as biomass recycling, sustainability and natural resource conservations. There is a market requirement for all agricultural products including coffee. However, scientific research is new and there is great need in key area as in organic system fertilizing. To evaluate planting fertilization with organic compound associated to bio-fertilizer leaf application on growth and coffee (Topázio MG-1190 cultivar) development, one study was established in greenhouse, at Agriculture Dept. of Federal University of Lavras coffee sector, from March 15 to October 4 of 2003. A randomized block design in factorial arrangement (5 x 5 + 3 factors) was used with four replications, using one plant per plot. First factor was organic compound rate/pot (110, 330, 550, 770 and 990g) mixed to 7,0 dm3 of soil/pot. The second bio-fertilizer "supermagro" monthly leaf applied at 0%, 3%, 6%, 12% and 24% concentration. Additional treatments were, organic fertilizer, organic + mineral and mineral fertilizer on soil application. Plant height, diameter at ground level (mm), stem node number, leaf area (cm2), leaf number, leaf dry weight, aerial part plant dry weight, total plant dry weight, as well as, macro and micronutrient leaf contents. Significant interaction occurred with lateral branch, leaf number, leaf dry weight, aerial part and total plant dry weight, Mg and B nutrient content and the best plant development from 702g to 770g of the compound/pot plus bio-fertilizer application from 14,45% to 16,38%. Increasing the compound rate, occurred N, K and Mg leaf content increasing, decreasing P and Ca leaf content, K/Ca competition reduction, B, Cu, Fe and Mn availability diminutions with increasing pH. Bio-fertilizer use was efficient in Mg, B and Cu as plant supplying.